Magmatic Signature in Submarine Hydrothermal Fluids Vented Offshore Ventotene and Zannone Islands (Pontine Archipelago, Central Italy) - Francesco Italiano; Davide Romano; Cinzia Caruso; Manfredi Longo; Andrea Corbo; Gianluca Lazzaro (Geofluids)
Geochemical investigations carried out on submarine hydrothermal fluids vented offshore the Pontine Islands (Tyrrhenian Sea) revealed the existence of gas vents to the W of Zannone Island and SW of Ventotene Island. The geochemical features of the CO2-rich gas samples show a clear mantle-derived signature with 3He/4He of 3.72-3.75 Ra and 1.33 Ra at Zannone and Ventotene, respectively. Gas geochemistry denotes how CO2-rich gases undergo fractionation processes due to CO2 dissolution to a variable extent favoring enrichment in the less soluble gas species, i.e., CH4, N2, and He. The carbon isotope composition of CO2, expressed as δ13C vs. V-PDB, ranges from -0.71 and -6.16‰ at Zannone to 1.93‰ at Ventotene. Preliminary geothermometric and geobarometric estimations indicate equilibrium temperatures in the range of 150-200°C at Zannone and >200°C at Ventotene besides H2O pressures in the range of 5 bar and 20 bar at Zannone and Ventotene, respectively. Although the latest volcanic activity at the Pontine Archipelago is dated Middle Pleistocene, the combination of the new geochemical information along with geothermometric estimations indicates that cooling magmas are likely releasing enough thermal energy to form an efficient hydrothermal system.